Alternatives to Alginate Impression Materials - C.M, AATHIRA.; MDS, DR. BALAJI GANESH S; SIVASWAMY, DR. VINAY (The journal of contemporary issues in business and government, 2020)
Introduction: The review is about alternatives to alginate impression material. It is an irreversible hydrocolloid used to study cast and fabricate models for intraoral appliances and is commonly used impression material. It is effective but hydrophilic which makes it difficult. Alginate impression materials produces an imprint which provides all the details which has good accuracy and undercut is also recorded. It is a most commonly used material in daily practice. The applications of alginates includes thickeners and stabilizers in the food, pharmaceutical and cosmetic industries. It is well tolerated by patients and accounts for the primary prosthetic, orthodontic and dental imprints.